Anemia Prevention in Adolescent Females With Lawrence W. Green Theory Approach: A Literature Review - Ismail, Mujiono; Aisah, Siti; Soesanto, Edy; Pranata, Satriya (Babali Nursing Research, 2025)
Background: The prevalence of anemia worldwide is very high, particularly in developing countries, including Indonesia. Adolescent girls are especially susceptible to anemia, with the monthly menstrual cycle being one of the contributing factors. This review aims to synthesize data by analyzing several articles that focus on the prevention of anemia in adolescent girls using the Lawrence W. Green theory approach. Methods: The method used for this article is a literature review of articles published between 2020 and 2024. The sources include Google Scholar, PubMed, and ScienceDirect, with the keywords "Anemia," "Prevention," "Adolescent girls," and "Lawrence W. Green's Theory." After the screening process, 15 articles were selected for review out of the 883 articles initially identified. Results: The findings indicate that individual behaviors vary widely, even among identical twins. Behavior does not always follow a predictable pattern, and the development of positive behavior is not solely determined by knowledge or positive attitudes. According to Lawrence W. Green's Theory, factors influencing actions or behaviors are classified into three categories: 1) Predisposing factors, 2) Enabling factors, and 3) Reinforcing factors. Conclusion: The prevention of anemia in adolescent girls is influenced by factors such as knowledge levels, attitudes, peer support, and the availability of health facilities.